2019
DOI: 10.1111/ecc.13066
|View full text |Cite
|
Sign up to set email alerts
|

Is ignorance bliss, or is knowledge power? When cancer healthcare professionals become cancer patients

Abstract: Cancer healthcare professionals who are diagnosed with cancer enter the patient journey with considerable illness‐specific and healthcare expertise, which may influence the nature of their experience. Insights gained from having personal cancer experience may also lead to changes in professionals' subsequent clinical practice. This study explored cancer professional‐patients' experiences of their own cancer diagnosis, changes in practice, and recommendations for cancer care improvements. Participants were curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
2
11
1
Order By: Relevance
“…A participant painfully recounted how at a regional referral hospital, she was told and was always left to administer phototherapy to herself, resulting in severe toxicities of the treatment due to lack of monitoring and supervision from the attending doctors. These findings differ from those of a study by Lagad et al, 3 who found, in Australia, HCPs cancer patients found it easy to navigate the healthcare system including receiving immediate free or subsidized, high-quality care delivered by experts. Similar disparities in accessing cancer care including palliative care, surgery, radiotherapy, and chemotherapy are reported in other large, global studies.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…A participant painfully recounted how at a regional referral hospital, she was told and was always left to administer phototherapy to herself, resulting in severe toxicities of the treatment due to lack of monitoring and supervision from the attending doctors. These findings differ from those of a study by Lagad et al, 3 who found, in Australia, HCPs cancer patients found it easy to navigate the healthcare system including receiving immediate free or subsidized, high-quality care delivered by experts. Similar disparities in accessing cancer care including palliative care, surgery, radiotherapy, and chemotherapy are reported in other large, global studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, some had to be advised by their healthcare colleagues to seek specialist attention, while others were prompted by their symptoms to seek further care. Lagad et al 3 similarly found HCPs who became ill with cancer received professional advice from colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contributors also examine the role of context and individual factors in the cancer experience. Lagad, Hodgkinson, and Newton‐John () applied a qualitative approach to unpack how cancer professional‐patients face unique needs, benefits and disadvantages due to their professional backgrounds. These narratives raise the importance of how we care for our colleagues (and ourselves) as well as how we might utilise these perspectives to improve the cancer care system.…”
mentioning
confidence: 99%